Canine atopic dermatitis - Craig, Mark (Henry Stewart Talks, 2019)
Environmental factors that can affect the pathogenesis, Association between the microbiome and CAD, Immune dysregulation as an influential factor, A history and clinical features of CAD, How to eliminate differentials, Allergy testing for specific allergens, Flare factors and how to avoid them, Pharmacological treatment options